2023
DOI: 10.1097/prs.0000000000010710
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blinded Randomized Control Trial Comparing Liposomal Bupivacaine and Plain Bupivacaine in Transversus Abdominis Plane For Deep Inferior Epigastric Artery Perforator (DIEP) Flap Breast Reconstruction

Abstract: ince 2000, there has been a 36% growth in breast reconstruction procedures in the United States. 1 Patient-reported qualityof-life studies suggest that women who undergo autologous breast reconstruction have increased satisfaction and psychosocial well-being. 2,3 Consequently, the number of deep inferior epigastric artery perforator (DIEP) flap procedures performed each year has doubled in the past Background: Pain control after autologous breast reconstruction is important for patient satisfaction and early r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…The current and previous studies support a reduction in opioid consumption with liposomal bupivacaine in DIEP flap breast reconstruction. Although the MMEs reported in this analysis were higher than those reported in a prior randomized controlled trial and retrospective single-center studies, 15,21,22,26 there are several differences between the previous studies and current analysis that could limit between-study comparisons of MMEs, including different study designs (eg, prospective versus retrospective, single-center versus claims databases of ≥300 medical centers), type of DIEP procedure (eg, unilateral versus bilateral, immediate versus delayed), differences in prior opioid exposure within selected patient populations, potential differences in liposomal bupivacaine administration method or dosing (eg, TAP blocks, local infiltration, paravertebral blocks), differing methodology and followup durations for opioid consumption measures, and varying components used in the overall study multimodal pain management regimens. Notably, the opioid data in the current analysis likely reflect a wide variety of opioidprescribing practices across the 300 or more medical centers included in the IQVIA linkage claims databases.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…The current and previous studies support a reduction in opioid consumption with liposomal bupivacaine in DIEP flap breast reconstruction. Although the MMEs reported in this analysis were higher than those reported in a prior randomized controlled trial and retrospective single-center studies, 15,21,22,26 there are several differences between the previous studies and current analysis that could limit between-study comparisons of MMEs, including different study designs (eg, prospective versus retrospective, single-center versus claims databases of ≥300 medical centers), type of DIEP procedure (eg, unilateral versus bilateral, immediate versus delayed), differences in prior opioid exposure within selected patient populations, potential differences in liposomal bupivacaine administration method or dosing (eg, TAP blocks, local infiltration, paravertebral blocks), differing methodology and followup durations for opioid consumption measures, and varying components used in the overall study multimodal pain management regimens. Notably, the opioid data in the current analysis likely reflect a wide variety of opioidprescribing practices across the 300 or more medical centers included in the IQVIA linkage claims databases.…”
Section: Discussioncontrasting
confidence: 76%
“…25 Another recent double-blind randomized controlled trial that compared TAP blocks with liposomal bupivacaine versus plain bupivacaine (as a component of an enhanced recovery after surgery protocol) for DIEP flap breast reconstruction found no significant differences between treatment groups in daily opioid consumption or pain scores through 1 week after surgery. 26 Select studies have assessed additional outcomes with liposomal bupivacaine versus comparators, including length of stay and healthcare resource utilization measures (eg, costs). Liposomal bupivacaine (LB) was associated with reduced length of stay, costs, and 30-day readmission rates in prior analyses combining abdominal and breast reconstruction procedures.…”
Section: Introductionmentioning
confidence: 99%
“…All included studies investigated transversus abdominis plane blocks, except for one that used quadratus lumborum block. For the primary outcome, four studies posted results on clinicaltrials.gov, with three appearing not to have completed the original target enrollment (one was recently published, 4 the other three not published), six studies reported no benefit of liposomal bupivacaine, and three studies reported benefit. Using the conservative Hartung-Knapp-Sidik-Jonkman method for random effects, the authors report no benefit of liposomal bupivacaine over plain bupivacaine in the primary outcome when pooling the results of 13 studies or in any of the secondary outcomes.…”
mentioning
confidence: 99%
“…The subcostal approach, which covers mainly T9–11 dermatomes, 8 would be more suitable for an upper abdominal surgery, 9 and a posterior approach to the transversus abdominis plane block or a rectus sheath block might have been more appropriate blocks to use and compare the two preparations of bupivacaine in this surgical model. Other included studies that used abdominally based breast reconstruction 4,10 may also not be the best models to evaluate transversus abdominis plane blocks, as these blocks would not likely cover the entire surgical area.…”
mentioning
confidence: 99%